Academic Communication Patterns in Response to Interpretational Differences at Institut Darul Qur’an Payakumbuh - Putri Adona; Ahmad Deski; Muhammad Rizqi; Novi Hendri (FiTUA: JURNAL STUDI ISLAM, 2026)
As a college characterised by a practical qur’anic curriculum, Institut Darul Qur’an Payakumbuh engages with diverse exegetical literature spanning several eras, fostering significant intellectual dynamism. This study aims to explore academic communication patterns between lecturers and students regarding interpretative differences. Adopting a descriptive qualitative method, data were gathered via questionnaires and observations of 48 respondents to capture their engagement with literature ranging from classical to modern periods. The findings reveal that communication is characterised by a robust discussion ethic (scoring 4.7/5.0), prioritising truth-seeking dialogue. Whilst intellectual openness and classical methodological authority are upheld, a gap persists in students’ academic dialectics, necessitating systematic strengthening. Ultimately, effective communication within the institution enhances academic quality and reinforces religious moderation when addressing diverse interpretations. Harmonising tradition and modernity within this dialogic space is essential for managing differing opinions; therefore, it is recommended that students critical dialectical skills be further developed to refine the existing intellectual ecosystem. This balance ensures that the institution remains a beacon for both scholarly rigour and harmonious religious discourse. This study contributes critical insights for higher education institutions in formulating policies regarding the integration of religious moderation values into the curriculum.